Поэтический и образный строй стихотворения Е.Л. Владимировой «Я всего лишь тюремный поэт...» - ГорбачевСкИй, чеСлав антоновИч (Acta Neophilologica, 2019)
This article analyzes one of the poems written by the Russian poetess Elena Vladimirova. The author protests against prisons and hard forced camps systems established by Joseph Stalin, in which Elena Vladimirova spent more than eighteen years. We focus on such features of the poem as a poetic and figurative system and images-sym-bols, time and space, and two main “points of view”: “the supervisor’s estate” and “the slave’s estate”. The conclusions of the analyzed poem may initially seem unexpected: the boundaries between freedom and imprisonment are very unstable and subtle in the totalitarian state.